A REVIEW OF EXPERIMENTAL STUDY AND PERFORMANCE OF FLAT PLATE SOLAR WATER HEATER WITH DIFFERENT FLOW RATES - Kumar Tripathi, Shiv; Aijaz, Mohammad Azim (International Journal of Research -GRANTHAALAYAH, 2016)
The analysis of thermal performance of the flat-plate collector includes parameters such as solar intensity, ambient temperature and configuration of flat-plate collectors etc. A Solar Water Heater are devices which are provides hot water for bathing, washing, cleaning, etc. using of solar energy. It is generally installed where sunlight are available. The solar energy is the most capable of the alternative energy sources. Solar energy is considered an attractive source of renewable energy that can be used for water hearing in both homes and industry.